Social anxiety symptoms - Ayyash-Abdo, Huda (2016)
The purpose of the study was to compare the frequency of social anxiety symptoms among young adults in Lebanon and young adults in the UK and to investigate the relationship between social anxiety, self-construals, and perceived social norms. A total of 680 young adults (312 from Lebanon and 368 from the UK) between the ages of 17 and 29 years were examined. All participants completed questionnaires used to measure social anxiety symptoms, self-construals, and reactions to perceived social norms. Lebanese young adults scored higher than UK participants on independent and interdependent self-construals. Compared to participants, Lebanese participants showed a greater acceptance of attention seeking behaviors. Though independent self-construal was negatively correlated with social interaction anxiety for both samples, cultural norms were negatively correlated with social anxiety only for the UK sample. The correlation between independent/interdependent self-construals and cultural norms/values was higher in the UK sample.